Impacts of Soil Freeze–Thaw Process and Snow Melting Over Tibetan Plateau on Asian Summer Monsoon System: A Review and Perspective - Wang, Chenghai; Yang, Kai; Zhang, Feimin (Frontiers in Earth Science, 2020)
Surface diabatic heating over the Tibetan Plateau (TP) is crucial for the onset and development of Asian summer monsoon (ASM), which is closely connected with the snow melting and freeze–thaw (SM-FT) processes in spring. This study reviews the recent processes about studies on the effects of SM-FT on the climate system over the ASM region. This review has shown that SM-FT in spring plays a dominant role in seasonal and inter-annual variations of surface diabatic heating over TP, which also have a significant relationship with the ASM activity. Moreover, the anomalies of SM-FT over TP significantly affect summer precipitation in Eastern China (EC). SM-FT in spring over TP would be a robust factor in the ASM system. The possible mechanism associated with the impacts of SM-FT on the summer general circulation in East Asia is also discussed. Under the climate change background, variations in regimes of frozen soil and snow have great potential effects on the climate in East Asia and around the globe. However, great uncertainties in the estimation of diabatic heating over TP (especially over the western TP) during spring still confine our understanding about the effects of TP thermal forcing on the ASM activity. It is suggested that improvement in the simulation of the SM-FT process in models is an effective approach for reducing the biases of climate projection in future.